1996
DOI: 10.1007/bf00198436
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic criteria in nonfunctioning pancreatic endocrine tumours

Abstract: To identify prognostic subgroups among non-functioning (nonsyndromic) pancreatic endocrine tumours, a series of 61 tumours were analysed systematically for macroscopic, histopathological and immunohistochemical variables potentially predictive of malignancy. High-grade nuclear atypia, elevated mitotic rate and multifocal necrosis allowed us to separate 5 poorly differentiated carcinomas from 56 well differentiated tumours. Among the latter, 29 well-differentiated carcinomas showing gross local invasion or meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(172 citation statements)
references
References 34 publications
12
155
1
3
Order By: Relevance
“…Validation of the prognostic ability of Ki-67 has shown differences in 5-year survival using a binary schema of !2 or O2%: pancreatic NENs (PNENs) showed 100 vs 54% survival at 5 years (La Rosa et al 1996); a mixed group of GEP-NENs showed 56 vs 14% and 90 vs 54%, and a mixed group of pancreatic, SI, and colorectal NENs showed 76 vs 29% (Arnold et al 2008a). More recently, the use of Ki-67 was defined for PNENs in a study on 1072 patients with at least 2 years of follow-up (Rindi et al 2012).…”
Section: Tissue Ki-67 Assessmentmentioning
confidence: 99%
“…Validation of the prognostic ability of Ki-67 has shown differences in 5-year survival using a binary schema of !2 or O2%: pancreatic NENs (PNENs) showed 100 vs 54% survival at 5 years (La Rosa et al 1996); a mixed group of GEP-NENs showed 56 vs 14% and 90 vs 54%, and a mixed group of pancreatic, SI, and colorectal NENs showed 76 vs 29% (Arnold et al 2008a). More recently, the use of Ki-67 was defined for PNENs in a study on 1072 patients with at least 2 years of follow-up (Rindi et al 2012).…”
Section: Tissue Ki-67 Assessmentmentioning
confidence: 99%
“…Finally, there is no histological tumour grading for welldifferentiated endocrine tumours of the digestive tract, although it has been tentatively developed for pancreatic and gastric tumours (La Rosa et al 1996, Rindi et al 1999a. Further, a number of clinicopathological criteria proved to be useful predictors of malignant behaviour (La Rosa et al 1996, Rindi et al 1999a and included: tumour size (larger tumours tend to be more aggressive); invasion of nearby tissue (pancreas or appendix) or deep wall invasion; angioinvasion and invasion of perineural spaces; presence of spotty necrosis; overt cell atypia; more than two mitoses in 10 microscopic high power fields (HPF); Ki-67 index of more than 100/10 HPF or more than 2%; loss of chromogranin A immunoreactivity or hormone expression; nuclear p53 protein accumulation; and aneuploid status of tumour cells.…”
Section: Differentiation Histology and Behaviourmentioning
confidence: 99%
“…Further, a number of clinicopathological criteria proved to be useful predictors of malignant behaviour (La Rosa et al 1996, Rindi et al 1999a and included: tumour size (larger tumours tend to be more aggressive); invasion of nearby tissue (pancreas or appendix) or deep wall invasion; angioinvasion and invasion of perineural spaces; presence of spotty necrosis; overt cell atypia; more than two mitoses in 10 microscopic high power fields (HPF); Ki-67 index of more than 100/10 HPF or more than 2%; loss of chromogranin A immunoreactivity or hormone expression; nuclear p53 protein accumulation; and aneuploid status of tumour cells. These variables should all be considered in assigning a tentative risk class for each specific case.…”
Section: Differentiation Histology and Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…EPTs have been recently stratified, on the basis of the WHO classification, in 3 categories: benign tumors, well-differentiated carcinomas with low-grade malignant behaviour and poorly-differentiated carcinomas with high grade malignant behaviour [10]. Malignancy is assessed by the presence of invasiveness of adjacent structures or viscera and/ or metastases or, in their absence, by the following criteria: vascular or perineural microinvasion, tumor size >4 cm., Ki 67 proliferative index >2%, presence of necrosis and/or clear cellular atypia, capsular penetration, mitotic rate >2, loss of chromogranin A (CgA) and calcitonin immunoreactivity, argyrophilia and nuclear p53 protein accumulation [11]. Surgeons approaching EPTs must firstly address the problem of a correct diagnosis that could be uncertain when facing a bulky pancreatic mass with charachteristics resembling the more common pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%